2019
DOI: 10.1175/bams-d-18-0337.1
|View full text |Cite
|
Sign up to set email alerts
|

In-Orbit Performance of the Constellation of CYGNSS Hurricane Satellites

Abstract: The NASA Cyclone Global Navigation Satellite System (CYGNSS) constellation of eight satellites was successfully launched into low Earth orbit on 15 December 2016. Each satellite carries a radar receiver that measures GPS signals scattered from the surface. Wind speed over the ocean is determined from distortions in the signal caused by wind-driven surface roughness. GPS operates at a sufficiently low frequency to allow for propagation through all precipitation, including the extreme rain rates present in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 42 publications
1
66
1
Order By: Relevance
“…In this study, a few quality control steps were applied to the Level 2 CYGNSS data v2.1. Data with the range corrected gain below 3 and the zenith sun angle lower than zero were removed to Previous studies found that CYGNSS measurements during TC overpasses can help in finding the correct center location, estimating the intensity, and constructing the wind distribution within the TC [40,47,48]. Hoover et al [46] also showed that synthetic CYGNSS data may be used to monitor westerly wind burst (WWB) events during MJO events.…”
Section: The 2018 January Mjo and Cygnss Observationmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, a few quality control steps were applied to the Level 2 CYGNSS data v2.1. Data with the range corrected gain below 3 and the zenith sun angle lower than zero were removed to Previous studies found that CYGNSS measurements during TC overpasses can help in finding the correct center location, estimating the intensity, and constructing the wind distribution within the TC [40,47,48]. Hoover et al [46] also showed that synthetic CYGNSS data may be used to monitor westerly wind burst (WWB) events during MJO events.…”
Section: The 2018 January Mjo and Cygnss Observationmentioning
confidence: 99%
“…The FDS is appropriate for most conditions, while the YSLF data can be used typically for the inner core of TCs. YSLF GMF was developed for conditions when the long-wave portion of the sea state has not responded fully to the local surface winds [40,41]. Figure 2 displays the sample data of the CYGNSS v2.1 YSLF (Figure 2a) product around 1500 UTC, and FDS product over-plotted on GPM IMERG rainfall ( Figure 2b) at around 1500 UTC, and the ASCAT wind speed ( Figure 2c) at 1448 UTC on 7 January 2018.…”
Section: The 2018 January Mjo and Cygnss Observationmentioning
confidence: 99%
See 2 more Smart Citations
“…The launch of the NASA Cyclone GNSS (CYGNSS) mission in Dec 2016 marked a significant opportunity to further validate and develop GNSS-R land applications. The primary mission of the eight satellite CYGNSS constellation is to measure ocean near surface winds for hurricane research [5]. However, multiple studies have recently demonstrated the use of CYGNSS land observations in surface water monitoring applications, including flood inundation [6] and near surface soil moisture [7,8].…”
Section: Introductionmentioning
confidence: 99%